Entrepreneurial ecosystems in theory and practice - Intenza, Marika (Emerald Publishing Limited, 2025)
Entrepreneurial ecosystems are affected by ongoing technological changes, evolving global economic conditions, and institutional frameworks that constantly reshape the entrepreneurial terrain. As entrepreneurial ecosystems progressively become focal to economic development strategies worldwide, there is a strong demand for updated insights that can inform decision-makers to implement best practices. Entrepreneurial Ecosystems in Theory and Practice offers a comprehensive and multi-dimensional understanding of entrepreneurial ecosystems through a blend of theoretical and practical insights, and comparative analyses. Italy has consistently experienced below-average performances on global entrepreneurship indexes. By providing detailed case studies - especially the in-depth analysis of Italy's entrepreneurial ecosystem and sector-specific dynamics - the book equips firms and other stakeholders with practical tools and strategies for improving their performance and integration within the surrounding entrepreneurial ecosystem. This will support informed decision-making regarding investments and policy formulation aimed at enhancing regional economic development and innovation. This series is dedicated to communicating innovative and multi-disciplinary new research that advances theory and practice in Entrepreneurial Behaviour. The series is focused on expanding the scope of Entrepreneurial Behaviour theory and analysis and enriching practice by encouraging multi-theoretical multi-cultural and multi-disciplinary approaches. Key issues to be explored in the series include cognition decision-making organisational behaviours and identifying creating and exploiting opportunities concerning new products services processes innovations or ventures from entrepreneurial perspective.